COMPARATIVE STUDY AND ANALYSIS OF PERFORMANCE REFRIGERATIONSYSTEMDRIVEN BY DIFFERENT ENERGYSOURCES - Guermit, T; Settou2, N (university of eloued -جامعة الوادي, 2019)
The present work concerns a study on mechanical compression refrigeration machines thatbased on the electric compressor, and absorption machine, were this work is focused onchoosing natural gas as a direct source in the refrigeration space; this logic was presentgeneral thermodynamic calculations of the two machines. The results show that quite goodvalues of the coefficient of performance of the new configuration of the absorptionrefrigeration machine and the study of the cost of each one, we can consider it encouragingfor the development of this device, which promises to bean alternative one hand to eliminatethe pressure in the electricity sector, and promises to be quite powerful economic and energypointof viewand side environment
article
Keywords: refrigeration system;mechanical;absorption machine;Energy;Cop.